Study guides

☆☆

Q: What is 9a plus 2b - 8a -3b?

Write your answer...

Submit

Still have questions?

Related questions

1a

9a + 3b - 11a - 4b = -2a -b

9a + 7b *remember to look and understand the letters!*

9a - 8a = a

12

3(3a+b)

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3

9a-a = 19+7a 8a = 19+7a 8a - 7a = 19 + 7a - 7a 1a = 19 a = 19

If: 9a = 18b Then: a = 2b

13

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b

2a+5a+9a = 16a

People also asked